2021
DOI: 10.1021/acs.joc.1c02295
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Bridged N-Heterocycles with Tertiary Carbon Center through Barbas Dienamine-Catalysis: Scope and Applications

Abstract: A direct aza-Diels–Alder reaction between 2-aryl-3H-indolin-3-ones and cyclic-enones has been developed to access chiral indolin-3-one fused polycyclic bridged compounds. This method proceeds via proline-catalyzed Barbas-dienamine intermediate formation from various cyclic-enones such as 2-cyclopenten-1-one, 2-cyclohexene-1-one, and 2-cycloheptene-1-one, followed by a reaction with 2-aryl-3H-indol-3-ones. Several indolin-3-ones fusing [2.2.2], [2.2.1], and [3.2.1] skeletons decorated with a tertiary carbon chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 85 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…However, the universal and appropriate strategy suitable for the enantioselective construction of chiral 2-alkenyl-substituted indolin-3-one derivatives is still lacking. In another aspect, the reported cases of 2-aryl-3 H -indol-3-ones (Scheme c) currently involved aza-Diels–Alder reaction, aza-Henry reaction, Mannich reaction, aza-Friedel–Crafts Reaction, and Ketimine–Ene Reaction . Despite the impressive advances, one universal asymmetric catalytic system involving aza-MBH reaction suitable for a family of ketimine substrates 2-aryl-3 H -indol-3-ones has not been developed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the universal and appropriate strategy suitable for the enantioselective construction of chiral 2-alkenyl-substituted indolin-3-one derivatives is still lacking. In another aspect, the reported cases of 2-aryl-3 H -indol-3-ones (Scheme c) currently involved aza-Diels–Alder reaction, aza-Henry reaction, Mannich reaction, aza-Friedel–Crafts Reaction, and Ketimine–Ene Reaction . Despite the impressive advances, one universal asymmetric catalytic system involving aza-MBH reaction suitable for a family of ketimine substrates 2-aryl-3 H -indol-3-ones has not been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, bicyclic structures such as isoquinuclidines represent another type of important heterocyclic moiety. 8 Besides different synthetic strategies, 8 in 1997 Yamaguchi et al reported an unexpected synthesis of 1,3-disubstituted benzoisoquinuclidines upon double nucleophilic addition and cyclization of N -acylated isoquinolinium triflate salts with allyl trimethylsilane (Scheme 1b). 9…”
mentioning
confidence: 99%